2011
DOI: 10.1161/circheartfailure.110.952200
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Coronary Sinus Serum Reveals Leucine-Rich α2-Glycoprotein as a Novel Biomarker of Ventricular Dysfunction and Heart Failure

Abstract: Background-Heart failure (HF) prevention strategies require biomarkers that identify disease manifestation. Increases in B-type natriuretic peptide (BNP) correlate with increased risk of cardiovascular events and HF development. We hypothesize that coronary sinus serum from a high BNP hypertensive population reflects an active pathological process and can be used for biomarker exploration. Our aim was to discover differentially expressed disease-associated proteins that identify patients with ventricular dysfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 34 publications
2
46
0
1
Order By: Relevance
“…7 We also reported that LRG is an effective serological marker for CD and UC. 10 An increase in serum LRG was also observed in other diseases such as rheumatoid arthritis, infection, heart failure, 12 and malignant diseases. 13 Moreover, our recent study clearly demonstrated an association between LRG upregulation and clinical activity of IBD, which was superior to conventional serological biomarkers.…”
Section: Introductionmentioning
confidence: 95%
“…7 We also reported that LRG is an effective serological marker for CD and UC. 10 An increase in serum LRG was also observed in other diseases such as rheumatoid arthritis, infection, heart failure, 12 and malignant diseases. 13 Moreover, our recent study clearly demonstrated an association between LRG upregulation and clinical activity of IBD, which was superior to conventional serological biomarkers.…”
Section: Introductionmentioning
confidence: 95%
“…However, one limitation of this approach was that the area under the curve (AUC) for LRG1 and the AUC of the combined markers (LRG1 + CA125) were not statistically different from the AUC of CA125 alone. Recently, LRG1 was found to be enriched in the urine of patients with appendicitis [39], as well as the serum of individuals with lung cancer [40], and heart failure [41]. It has also been suggested as a biomarker of ulcerative colitis [42].…”
Section: Resultsmentioning
confidence: 99%
“…A potential explanation may be cardiomyolisis (muscle tissue breakdown) of the heart with formation of creatine that further metabolizes to creatinine (Watson et al. ; Liu et al. ).…”
Section: Discussionmentioning
confidence: 99%